With strings attached: Grandparent-provided child care and female labor market outcomes - Eva García-Morán; Zoë Kuehn (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Grandparents are regular providers of free child care. Similar to other forms of child care, availability of grandparent-provided child care affects fertility and labor force participation of women positively. However, grandparent-provided child care requires residing close to parents or in-laws which may imply costly spatial restrictions. We find that mothers residing close to parents or in-laws have lower wages and that the probability of having to commute increases if relatives provide child care. We build a model of residence choice, fertility, and female labor force participation that can account for the observed relationships. We simulate our model to analyze how women's decisions would change if the availability of grandparent-provided child care or family policies were altered. We nd that if child care subsidies were raised to the Swedish level, fertility and mothers' labor force participation would increase, while mobility would remain unchanged. The absence of grandparents, on the other hand, would increase mobility, while it would only have limited negative e ects on aggregate fertility and labor force participation.
Keywords: J13; J61; H42; R23; 330; grandparent-provided child care; fertility; labor force participation; spatial restrictions; regional labor markets